Appropriate cut-off level of BMI for screening in Thai adults - Lakkana Thaikruea (2018)
Objective: A cut-off level of Body Mass Index (BMI) for cardiovascular risk factors is controversial for its appropriateness in Asians. The present study aimed to determine the appropriate BMI cut-off level for Thai Adults. Material and Method: 127 out of 387 teachers of at least 35 years of age from Phuket participated in the present study. Participants completed self-administered questionnaires, and had physical examination and blood drawn for lipid profile. Results: In multivariate analysis, participants with BMI ≥ 23 kg/m2were 2.7 (95%CI; 1.2, 6.1), 5.4 (2.3, 12.6), 5.1 (1.5, 16.0), and 7.2 (1.5, 34.1) times more likely to have total cholesterol ≥ 240 mg/dl, high-density-lipoprotein < 40 mg/dl, low-density-lipoprotein ≥ 160 mg/dl, and total cholesterol to HDL ratio > 5.0, respectively. Conclusions: For screening/education program, the BMI of 23 kg/m2may be an appropriate cut-off level for being overweight. To support this finding, further studies in other regions and other populations of Thailand are needed.